Chlamydia trachomatis genotypes A and B from urogenital specimens of patients in Spain: molecular characterization. (August 2018) - Piñeiro, L.; Isaksson, J.; Zapico, M.; Cilla, G.; Herrmann, B.
Abstract: Objectives: Chlamydia trachomatis ompA genotypes A and B, primarily associated with trachoma, were unexpectedly detected in urogenital samples of patients in Spain, a trachoma-free country. In this study, we aimed to explain this finding using analysis of organotropism-related genes and a multilocus sequence typing (MLST) technique. Methods: C. trachomatis genotypes A or B were detected in 8/930 (0.9%) infection episodes between 2006 and 2012. In these strains, organotropism-related genes (polymorphic membrane protein gene H, tryptophan synthase gene A, CTA0934, and cytotoxin) were studied. Further, the strains were analysed by MLST, using a polymerase chain reaction that amplifies five highly variable genomic loci ( hctB, CT058, CT144, CT172, and pbpB ). Amplicons were sequenced and phylogenetic analysis was conducted. Results: Seven strains were detected in the eight infection episodes (in one patient, an identical strain being found in two episodes). Analysis of organotropism-related genes showed that these strains shared genetic features characteristic of genitotropic genotypes but not of trachoma strains. Three strains of genotype A showed a unique and new MLST-sequence type (ST551, allele profile 8-8-2-27-69). The four strains of genotype B belonged to ST138. Conclusions: C. trachomatis ompA genotypes A and B associated with trachoma, but detected sporadically in urogenital samples in trachoma-free countries, may be the result of recombination between strains adapted to trachoma and strains adapted to sexual transmission.